Window correction at time series realization of the narrow-band gaussian stochastic process - Величко, Анатолий Федорович; Величко, Дмитрий Анатольевич; Вичкань, Алексей Валерьевич; Нетребенко, Константин Владимирович (Eastern-European Journal of Enterprise Technologies, 2014)
The paper deals with forming random realizations of a narrowband, stochastic stationary process as time functions on the interval, limited by the received signal duration. Independent values of the envelope and phase functions are used during the formation. For them nodal points with a uniform and the Rayleigh distribution are defined by the multiplicative congruent method. They are set within the given interval at distances greater than the correlation interval. Intermediate points are determined using a widely used spline interpolation. Herewith, there are values that go beyond the theoretical distributions of the amplitude and phase. Using the Hanning window function, the correction of random functions in these areas is introduced. This allows bringing the distribution of the envelope and the phase of the generated realizations to the theoretical laws. The statistical properties of the generated realizations before and after the window correction are studied.